A case report of unusually long lag time between immunotactoid glomerulopathy (itg) diagnosis and diffuse large B-cell lymphoma (DLBCL) development. Issue 1 (December 2016) - Khandelwal, Aditi; Trinkaus, Martina; Ghaffar, Hassan; Jothy, Serge; Goldstein, Marc
Abstract Background Immunotactoid glomerulopathy (ITG) is a rare cause of proteinuria characterized by organized microtubular deposits in the glomerulus. ITG has been associated with underlying lymphoproliferative disorders and any renal impairment may be reversible with treatment of the concomitant hematologic malignancy. This case is the first reported in literature where diffuse large B cell lymphoma developed two years following the initial ITG diagnosis. Case presentation A 55-year-old woman with a history of well-controlled diabetes mellitus and thalassemia trait presented with proteinuria (830 mg/day) in 2010. Initially, she was managed with renin-angiotensin-aldosterone-system blockade. In 2012, the proteinuria worsened (4.3 g/day) and a renal biopsy showed immunotactoid glomerulopathy (Fig. 1). Despite extensive work up, no lymphoproliferative disorder was initially found. In January 2014, the patient presented with a soft-palate mass found on biopsy to be diffuse large B-cell lymphoma. She received 6 cycles of R-CHOP, 4 cycles of high dose methotrexate chemotherapy for CNS prophylaxis and 30 Gy of Intensity Modulated Radiation Therapy. Follow-up revealed complete remission of diffuse large B-cell lymphoma and resolution of proteinuria from the ITG. Conclusion As we recognize that patients with ITG may develop hematopoietic neoplasms, close long-term monitoring is important. Moreover, treatment of the lymphoproliferative disorder can allow for complete remission of ITG.